The Mapping of Rattan Weaving Craft Business Modeling Gohong Village, Pulang Pisau Regency, Central Kalimantan - Junaidah Junaidah; Adnan Ardhana; Mimi Salminah; Dian Cahyo Buwono (Jurnal GALAM, 2022)
This study aims to mapping the business models of rattan woven craft venturess in Gohong Village, Kahayan Hilir District, Pulang Pisau Regency, Central Kalimantan. This research is a qualitative research with a case study technique. The analytical method used is the Business Model Canvas (BMC) approach with 9 (nine) block elements. The research results showed that the customers of the rattan business were segmented markets which were divided into three groups, including demographic, geographic and psychographic. The propositions of value that given were the quality, and variety of types and motifs of the products. Additionally, marketing channels were carried out both directly and indirectly by using several market players. The customer relationship developed in the form of personal assistance; meanwhile, revenue streams were derived from the product’s sales. Key resources consist of physical assets, group-owned capital, and trained human resources. The mainactivities in the rattan weaving craft business consisted of rattan cultivation, processing of raw rattan for ready-to-weave, weaving of the rattan, and selling of the products. The key partnerships included manufacturers of raw materials , sewing equipment shops, and synthetic leather shops. Finally, the cost structure included several costs for suppliying raw materials, transportation, communications and production equipment. The positive business model elements include broad market segments, quality products and trained human resources that must be maintained and developed. The negative business model elements such as limited capital and raw materials must be resolved.